Compositional and Quantitative Insights Into Bacterial and Archaeal Communities of South Pacific Deep-Sea Sponges (Demospongiae and Hexactinellida) - Georg Steinert; Georg Steinert; Kathrin Busch; Kristina Bayer; Sahar Kodami; Pedro Martinez Arbizu; Michelle Kelly; Sadie Mills; Dirk Erpenbeck; Dirk Erpenbeck; Martin Dohrmann; Gert Wörheide; et al. (Frontiers in Microbiology, 2020)
In the present study, we profiled bacterial and archaeal communities from 13 phylogenetically diverse deep-sea sponge species (Demospongiae and Hexactinellida) from the South Pacific by 16S rRNA-gene amplicon sequencing. Additionally, the associated bacteria and archaea were quantified by real-time qPCR. Our results show that bacterial communities from the deep-sea sponges are mostly host-species specific similar to what has been observed for shallow-water demosponges. The archaeal deep-sea sponge community structures are different from the bacterial community structures in that they are almost completely dominated by a single family, which are the ammonia-oxidizing genera within the Nitrosopumilaceae. Remarkably, the archaeal communities are mostly specific to individual sponges (rather than sponge-species), and this observation applies to both hexactinellids and demosponges. Finally, archaeal 16s gene numbers, as detected by quantitative real-time PCR, were up to three orders of magnitude higher than in shallow-water sponges, highlighting the importance of the archaea for deep-sea sponges in general.